2011
DOI: 10.1167/iovs.11-8332
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Serial Imaging of Regenerating Corneal Nerves after Surgical Transection in Transgenic Thy1-YFP mice

Abstract: Although corneal NFD recovers to normal levels by 8 weeks after nerve transection, the arrangement of regenerated nerves is abnormal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 31 publications
3
40
0
Order By: Relevance
“…Such interest extends also to the eye, and in recent years, many publications have used mice to analyze normal and pathologic ocular processes, including those affecting the sensory innervation of the corneal surface. [1][2][3] As a result of these studies, the distribution and architecture of mouse corneal sensory innervation is reasonably well known, confirming that it follows the morphologic pattern of corneal nerve branching described in other mammalian species, 4,5 although remarkable differences exist in nerve density between mice strains. 4 Additionally, the corneal innervation of mice has been used to explore the origin and trophic dependence of peripheral sensory nerves during prenatal development 6 and postinjury nerve regeneration in adults, 3,7,8 as well as age-dependent changes in the architecture and function of corneal nerves.…”
supporting
confidence: 73%
“…Such interest extends also to the eye, and in recent years, many publications have used mice to analyze normal and pathologic ocular processes, including those affecting the sensory innervation of the corneal surface. [1][2][3] As a result of these studies, the distribution and architecture of mouse corneal sensory innervation is reasonably well known, confirming that it follows the morphologic pattern of corneal nerve branching described in other mammalian species, 4,5 although remarkable differences exist in nerve density between mice strains. 4 Additionally, the corneal innervation of mice has been used to explore the origin and trophic dependence of peripheral sensory nerves during prenatal development 6 and postinjury nerve regeneration in adults, 3,7,8 as well as age-dependent changes in the architecture and function of corneal nerves.…”
supporting
confidence: 73%
“…41 Considering the numerous positive and negative regulators influencing the final trajectory and elongation of axons after injury, the slow and incomplete recovery of the prelesion innervation architecture after PRK is not surprising. 42 Our study revealed that the appearance of sprouting axons within the injured area does not imply an immediate and parallel recovery of their function. In fact, we observed that corneal sensory terminals of different modality required variable times to recuperate responsiveness to their natural stimuli.…”
Section: Discussionmentioning
confidence: 62%
“…We have previously reported that changes in subbasal nerve pattern may occur with sequential stereofluorescence microscope imaging in thy1-YFP mice corneas, even without any intervention. 15 The deeper stromal nerve pattern and density remained constant. Therefore, we reasoned that because stromal nerves are less prone to variability in sequential measurements, changes in their pattern and density will be indicative of true neurotoxicity.…”
Section: Discussionmentioning
confidence: 92%
“…29 We, as well as others, have reported that regenerating nerves in the cornea do not follow pre-existing tracks; therefore, the appearance of new fluorescent nerve fibers in a new pattern signifies nerve regeneration. [14][15][16] We visualized two forms of stromal nerve neurotoxicity. Reversible neurotoxicity (axonopathy) was characterized by Western blot analyses of corneal lysate showed an increase in abundance of proteins associated with inflammation (IL6 and CD3) at 1 week and reduced abundance at 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation